Kajian Kebijakan Proses Pengambilan Keputusan di Perguruan Tinggi di Era Revolusi Industri - azis, muhammad; Abduh, Amirullah (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
This article aims to describe the process of decision-making and the effective method of disseminating the decision result. This descriptive research use questionannaires and interviews for data collection. The result of the study shows that the process of decision-making is predominantly done through the formal process of the combination of top-down and bottom up mechanisms. The approach for dissemination of meeting result is done through traditional approach of formal meeting and social media. The implication of this process is that the formal meeting is the best best possible option in the process of decision-making. This mechanism allows every participant to contribute to providing suggestions in creating effective decision-making. This research contributes to the development and the debates on the policy and mechanism of decision-making process